2019
DOI: 10.1007/s11135-019-00955-w
|View full text |Cite
|
Sign up to set email alerts
|

Happiness perception in Spain, a SEM approach to evidence from the sociological research center

Abstract: In the current study, we examined the relationship between perceived person happiness and factors that influence this perception, also, is inferred that life satisfaction is influence by happiness. Among 2494 Spaniards individuals of both sexes, we found that these individuals valued political situation, economic situation and socio-demographic characteristics to have a strong association in that order, with happiness and that this last construct is a fundamental factor to life satisfaction. The importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…It is generally accepted that happiness is found, on the one hand, in the individual satisfaction that is enjoyed in the long term when our achievements and purposes are fulfilled—eudemonism—and, on the other hand, in the pleasure of carrying out rewarding activities in the short and medium term—hedonism (Huta and Waterman, 2014 ). Based on this philosophical and psychological adage, an important volume of scientific work emerges focused on exploring that the meaningful originates when people gravitate their individual efforts in undertaking social activities or actions that contribute to the common good and therefore to the collective happiness of the citizens (Duckworth et al, 2005 ; O'Donovan and Sheikh, 2014 ; Núñez-Barriopedro et al, 2020 ). In line with this research, the literature shows that meaningful, at the microindividual level, should be associated not only with negative, depressive, and unhealthy experiences, but also with positive and optimistic emotions.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that happiness is found, on the one hand, in the individual satisfaction that is enjoyed in the long term when our achievements and purposes are fulfilled—eudemonism—and, on the other hand, in the pleasure of carrying out rewarding activities in the short and medium term—hedonism (Huta and Waterman, 2014 ). Based on this philosophical and psychological adage, an important volume of scientific work emerges focused on exploring that the meaningful originates when people gravitate their individual efforts in undertaking social activities or actions that contribute to the common good and therefore to the collective happiness of the citizens (Duckworth et al, 2005 ; O'Donovan and Sheikh, 2014 ; Núñez-Barriopedro et al, 2020 ). In line with this research, the literature shows that meaningful, at the microindividual level, should be associated not only with negative, depressive, and unhealthy experiences, but also with positive and optimistic emotions.…”
Section: Introductionmentioning
confidence: 99%
“…The variable of happiness is also considered (Foncubierta-Rodríguez et al, 2020). Thus, the two most commonly used items to measure this parameter were selected (Núñez-Barriopedro et al, 2020). In addition to these two questions, four other questions were added relating to turnover, profitability, operating result and profit on a Likert scale of 0 to 5 points (AECA, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…One reason for this phenomenon is that this line of research is still in its emerging stage. The growing interest in this line of research highlights that happiness is one of the main assets that managers of organisations possess to cultivate their employees' subjective wellbeing (Basinska and Rozkwitalska, 2020;Núñez-Barriopedro et al, 2020). In this way, internal customers considerably increase their creativity, productive effectiveness, motivation, etc.…”
Section: Happiness Managementmentioning
confidence: 99%
“…Both characteristics are more common in managerial and professional occupations than routine jobs. Furthermore, previous literature in Spain found that political perception, economic situation, and socio-demographic characteristics strongly influenced levels of happiness ( Núñez-Barriopedro et al, 2020 ), as well as climate variables ( Cuñado & Pérez, 2013 ) and educational level ( Cuñado & Pérez, 2012 ).…”
Section: Introductionmentioning
confidence: 98%